Dynamic performance improvement of single‐phase PWM converters with power hysteresis control scheme. Issue 12 (13th August 2018) - Liu, Bi; Song, Wensheng; Ma, Junpeng; Feng, Xiaoyun; Li, Wei
Abstract : This study presents a direct power control (DPC) scheme with pulse width modulation module and two hysteresis comparators, for the application in single‐phase PWM converters to overcome the drawbacks of conventional proportion‐integration‐based DPC (PI‐based DPC), including poor dynamic performance and complexity of tuning PI parameters. According to the outputs of inner‐loop power hysteresis controllers, the proposed DPC scheme divides d–q reference frame into four sectors. In each sector, the dynamic power components are estimated to be equivalent as the outputs of PI controllers in PI‐based DPC. The proposed DPC scheme provides a new solution of non‐linear hysteresis control to achieve fast dynamic performance with constant switching frequency. Additionally, due to inductance parameter mismatch, the effect on powers is analysed in detail, and an inductance parameter on‐line estimation method is present and discussed. A comprehensive comparison of conventional table‐based DPC, PI‐based DPC and the proposed DPC methods has been conducted in this study, including steady‐state performance with respect to different factors, and dynamic response under different extreme conditions. The experimental results have verified the effectiveness of the proposed DPC scheme.